PENDIDIKAN NILAI DALAM MEMANUSIAKAN MANUSIA - Jeditia Taliak (TANGKOLEH PUTAI, 2018)
Education in human development and humanizing human beings is certainly expected to be done through the education process (school) which is followed by the students in particular but also for society in general. Society as a supporter and implementer of education itself must provide motivation. therefore, through educational institutions (schools) both public and private, society in general, but also learners are equipped with "value education" as an integral part of ourselves as human beings. With "Value education" can humanize people in the context. Good "Values" built into family, society, nation and State. Values are a top priority for educators in performing their main tasks, both at home as parents, but also in school as teachers.